Pengaruh Pijat Oksitosin Terhadap Pengeluaran Produksi ASI pada Ibu Postpartum di PMB Eka Rini Kecamatan Kalirejo Lampung Tengah - Sudiar, Naning; Kristiana, Dita (Abdi Geomedisains, 2024)
The coverage of exclusive breastfeeding in infants 0-6 months in Lampung province was 70.1%. Coverage in Central Lampung district was 65.2% of the achievement target of 80%. One of the factors that influenced the failure of exclusive breastfeeding was the delay in milk production after delivery. The oxytocin massage technique is one of the efforts to overcome the uneven production of breast milk. To find out the Effect of Oxytocin Massage on the Expenditure of Breast Milk Production in Post-Partum Mothers at Eka Rini Maternal Clinic, Kalirejo District, Lampung. This study applied quantitative research, and the design used in this research was a Quasi Experiment with one group pre-test and post-test design approach. The population in this study were all postpartum mothers at Eka Rini Maternal Clinic, Sinar Sari Village, Kalirejo District, Central Lampung Regency, as of July 2022, totalling 12 respondents. In this study the sampling technique used total sampling. Based on statistical tests, a p-value of 0.013 was obtained or a p-value <0.05, which means that there is an effect of oxytocin massage on breast milk production in postpartum mothers at Eka Rini Maternal Clinic, Kalirejo District, Lampung. There was an effect of oxytocin massage on the production of breast milk production in postpartum mothers. It is better to do regular oxytocin massages during the postpartum period to help facilitate breastfeeding, and nutritional intake and factors supporting breast milk production must also be maintained so that breast milk production can always be smooth and not hinder breastfeeding to the baby.